Test-retest & Inter rater Reliability of Persian version of Pediatric Balance Scale in Children with Spastic Cerebral Palsy - Alimi, Elnaz; Kalantari, Minoo; Nazeri, Ahmadreza; Akbarzade Baghban, Alireza (Iranian Journal of Child Neurology, 2019)
Objective: Children affected with spastic cerebral palsy have a lot of difficulties in terms of movement and balance. Balance is one of the necessary variables of movement, which facilitates functional skills. The aim of this inter rater & test-retest reliability study relating to Pediatric Balance Scale (PBS) for children withspastic cerebral palsy, was based on mild to moderate motor impairment or loss of movement. Materials and Methods: <span style="font-size: 12pt; font-family: ’Times New Roman’,’serif’; line-height: 107%; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: FA;">In this analytical-descriptive research performed in the rehabilitation centers, south of Tehran, Iran in 2016, psychometric method was used. For investigating the inter-rater reliability, two examiners performed the scale simultaneously with 50 children with spastic cerebral palsy. Moreover, to investigate the test-retest reliability, the scale was implemented by one examiner, in two different sessions, among 50 children with spastic cerebral palsy. There was a two-week period between the first and the second session. Results : The inter rater reliability (ICC = 0/99) as well as the test-retest reliability (1/100) was quite high Conclusion PBS is appropriate for measuring functional balance in children with spastic cerebral palsy with mild to moderate motor impairment.